Sugar-Sweetened Soda Consumption Increases Diabetes Risk Among Mexican Women. Issue 5 (29th April 2019) - Stern, Dalia; Mazariegos, Mónica; Ortiz-Panozo, Eduardo; Campos, Hannia; Malik, Vasanti S; Lajous, Martin; López-Ridaura, Ruy
ABSTRACT: Background: Epidemiological evidence supports an association between sugar-sweetened soda consumption and diabetes. However, evidence regarding this association is limited in countries that have recently undergone a nutritional transition. Objective: We estimated the association between sugar-sweetened soda consumption and incident diabetes. We also determined if the association between sugar-sweetened soda and diabetes differs as a result of early life factors and potential genetic susceptibility. Methods: We used data from the Mexican Teachers' Cohort including 72, 667 women aged ≥25 y, free of diabetes, cardiovascular disease, and cancer at baseline. We assessed sugar-sweetened soda consumption using a validated food frequency questionnaire (FFQ) at baseline. Diabetes was self-reported. We used Cox proportional hazard regression models to estimate the association between quintiles of sugar-sweetend soda and diabetes. We also estimated the associaiton by increasing one serving per day (355 mL) of sugar-sweetened soda. We conducted prespecified subgroup analysis by potential effect modifiers, namely markers of energy balance of early life factors, family history of diabetes, and Amerindian admixture. Results: During a median follow-up of 2.16 y (IQR 0.75–4.50) we identified 3, 155 incident cases of diabetes. The median consumption of sugar-sweetened soda was 1.17 servings per day (IQR 0.47– 4.00). In multivariable analyses, comparing extreme quintiles showed that higher sugar-sweetened soda consumption was associated with diabetes incidence (HR = 1.32; 95% CI: 1.17, 1.49), and each additional serving per day of sugar-sweetened soda was associated with an increase of 27% in diabetes incidence (HR = 1.27; 95% CI: 1.16, 1.38). The soda–diabetes association was stronger among women who experienced intrauterine and childhood over-nutrition (high birth weight, no short stature, higher adiposity in premenarche, and higher adiposity at age 18–20 y old). Conclusion: Sugar-sweetened soda consumption is associated with an increased risk of diabetes among Mexican women in a magnitude similar to that reported in other populations. The stronger association among individuals with markers of early life over-nutrition reinforce the need for early life interventions.